Sesotho Is Still A Marginalised Language - Koai, Mojalefa; Fredericks, Brenton Grant (Southern African Linguistics and Applied Language Studies, 2019)
This article reports on the progress (or lack thereof) regarding the use of Sesotho as an official medium of communication in selected government departments in the Free State Provincial Government (FSPG). In South Africa, provincial governments are required to implement language policies that promote multilingualism. The aim is to develop previously marginalised languages such as Sesotho, isiXhosa and isiZulu, among others, so that they have equal status to English and Afrikaans. A mixed-method design was used to guide the research process and purposive sampling to ensure that participants made a valuable contribution to this study. We are concerned that despite efforts being made to reduce the gap between official languages such as English and Afrikaans and the previously marginalised languages, there is no real progress in this regard. The results of this study reveal that Sesotho, as a previously marginalised language, is still underutilised in government departments. Evidence suggests that the results of this study be used as a guide for the formulation and implementation of language policies and procedures to address this problem.
Article